Endothelial/Epithelial Mesenchymal Transition in Ascending Aortas of Patients With Bicuspid Aortic Valve - Maleki, Shohreh; Poujade, Flore-Anne; Bergman, Otto; Gådin, Jesper R.; Simon, Nancy; Lång, Karin; Franco-Cereceda, Anders; Body, Simon C.; Björck, Hanna M.; Eriksson, Per (Frontiers in Cardiovascular Medicine, 2019)
Thoracic aortic aneurysm is the progressive enlargement of the aorta due to destructive changes in the connective tissue of the aortic wall. Aneurysm development is silent and often first manifested by the drastic events of aortic dissection or rupture. As yet, therapeutic agents that halt or reverse the process of aortic wall deterioration are absent, and the only available therapeutic recommendation is elective prophylactic surgical intervention. Being born with a bicuspid instead of the normal tricuspid aortic valve is a major risk factor for developing aneurysm in the ascending aorta later in life. Although the pathophysiology of the increased aneurysm susceptibility is not known, recent studies are suggestive of a transformation of aortic endothelium into a more mesenchymal state i.e. an endothelial-to-mesenchymal transition in these individuals. This process involves the loss of endothelial cell features, resulting in junction instability and enhanced vascular permeability of the ascending aorta that may lay the ground for increased aneurysm susceptibility. This finding differentiates and further emphasizes the specific characteristics of aneurysm development in individuals with a bicuspid aortic valve. This review discusses the possibility of a developmental fate shared between the aortic endothelium and aortic valves. It further speculates about the impact of aortic endothelium phenotypic shift on aneurysm development in individuals with a bicuspid aortic valve and revisits previous studies in the light of the new findings.